Range quality assurance measurements for clinical and FLASH proton beam therapy using the quality assurance range calorimeter - Shaikh, Saad; Escribano-Rodriguez, Sonia; Radogna, Raffaella; Saakyan, Ruben; Manger, Sam; Henthorn, Nicholas; Warmenhoven, John-William; Taylor, Michael; Jolly, Simon (Frontiers in Oncology, 2025)
ObjectiveThis work demonstrated the design and performance of a full-sized clinical prototype of the Quality Assurance Range Calorimeter (QuARC): a segmented large-volume scintillator-based detector for fast, accurate proton range quality assurance (QA) measurements.Materials & methodsThe detector used 128 scintillator sheets of size 105 × 105 × 3 mm arranged into 4 modules of 32 sheets, where each sheet was directly coupled to a photodiode. Fast analogue-to-digital conversion facilitated measurement of scintillator sheet light output to 20-bit precision at 6 kHz, with a dynamic range of up to 350 pC.ResultsProton range measurements with the full-size detector were performed at the proton therapy research facility based at The Christie at clinical dose rates, corresponding to ∼1 nA nozzle current, where the range accuracy of the QuARC was found to be within 0.4 mm of facility reference across the full clinical energy range. The QuARC successfully performed range measurements of the 245 MeV beam at FLASH dose rate (∼50 nA nozzle current), where the fitted range agreed with the clinical current measurement to 0.3 mm. Preliminary results show charge linearity of the detector to be within 3%.ConclusionsThe QuARC has been shown to be a promising candidate for fast, accurate range QA at conventional clinical dose rates and thanks to its high precision and dynamic range, has been shown to also be viable at FLASH dose rates. Future work will investigate improving the accuracy and stability of the calibration process by optimising the scintillator sheet light output and mechanical setup.